2020
DOI: 10.3390/ijerph17217745
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Cardiorespiratory Responses of Semiprofessional Football Players in Repeated Ajax Shuttle Tests and Curved Sprint Tests, and Their Relationship with Football Match Play

Abstract: In this study, the Ajax Shuttle Test (AST) and the Curved Sprint Test (CST) were conducted on semiprofessional football players to evaluate (1) their test performance, (2) the extent of anaerobic glycolysis by measuring blood lactate, (3) performance decrement and onset of fatigue, and (4) the correlation between selected physiological variables and test performance. Thirty-two semiprofessional Polish football players participated in this study. Both AST and CST were conducted on an outdoor football ground and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In the present study, the authors found correlations between fatigue and YYIR1 test results ( p < 0.004; Figure 4 ). This finding is supported by Gabrys et al [ 57 ], who concluded that the anaerobic glycolytic system is more sensitive to long, repetitive sprints, highlighting that RSA is a suitable strategy for avoiding insufficient aerobic energy systems, which lead to early decreases in performance [ 57 ]. All of these results indicate the value of forecasting Pmax from ADD and ABD isometric strength values (r = 0.53 and r = 0.55, respectively), Pmax from ABD values (r = 0.48), and fatigue from YYIR1 (r = −0.53).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present study, the authors found correlations between fatigue and YYIR1 test results ( p < 0.004; Figure 4 ). This finding is supported by Gabrys et al [ 57 ], who concluded that the anaerobic glycolytic system is more sensitive to long, repetitive sprints, highlighting that RSA is a suitable strategy for avoiding insufficient aerobic energy systems, which lead to early decreases in performance [ 57 ]. All of these results indicate the value of forecasting Pmax from ADD and ABD isometric strength values (r = 0.53 and r = 0.55, respectively), Pmax from ABD values (r = 0.48), and fatigue from YYIR1 (r = −0.53).…”
Section: Discussionmentioning
confidence: 60%
“…Although it was declared that straight sprinting is the most frequent action taken before goals, both for scoring and assisting players [ 51 ], the current trend highlights that sprints during soccer games are curvilinear [ 58 , 59 , 60 ]. As such, they may lead to different demands than straight sprints [ 57 ]. Therefore, further studies should assess the main determinants of curvilinear sprinting performance during RSA tests.…”
Section: Discussionmentioning
confidence: 99%
“…The post-exercise lactate concentrations detected in our study (biochemical and NMR analysis) potentially provide a window into the complex interplay of active energy systems during a soccer game ( 59 ). The varied motor skills demonstrated by soccer players, each demanding distinct energy delivery, might result in different lactate responses post-game.…”
Section: Discussionmentioning
confidence: 92%
“…The present study revealed negative correlations between high-intensity decelerations/accelerations and HRR. A greater cardiorespiratory capacity was previously suggested to allow players to produce a higher volume of low- and high-intensity accelerations during a match ( Gabrys et al, 2020 ; Osgnach et al, 2010 ). Positive correlations between decelerations/accelerations and HRR should be expected.…”
Section: Discussionmentioning
confidence: 99%